KUALITAS SEMEN SAPI LIMOUSIN PADA PENGENCER YANG BERBEDA SELAMA PENDINGINAN - Veronica Devita Bunga; Trinil Susilawati; Sri Wahjuningsih (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2014)
This study was done to evaluate quality of Limousin’s semen during chilled preservation. The characteristic of spermatozoa were easily damaged, so that they were necessary to protect viability of spermatozoa. Addition of extender was conducted to determine quality and viability of spermatozoa. Each extender were added Egg Yolk as diluents cryopreservation, the treatment were devided in to three groups, they were ; P0 (CEP-2 + 10% Egg Yolk), P1 (Tris Aminomethane + 20% EggYolk), P2 (Skim + 10% Egg Yolk). The result showed that Tris Aminomethane + 20% Egg Yolk gave the best effect on maintaining quality of spermatozoa (motility, viability and abnormality). The motility in three extender at 24h was high significant different (P<0,01). Furthemore, the Viability and abnormality showed high significant different (P<0,01) since first time evaluation at 0h until 24h. Tris Aminomethane showed the best result among others due to the addition of 20% Egg Yolk, as we know that Egg Yolk was an extracellular cryoprotectan to protect and nourish spermatozoa during chilling preservation. Keyword : Egg Yolk, CEP-2, Tris Aminomethane, Skim,